2009
DOI: 10.1080/03009740902932835
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three rheumatoid arthritis disease activity scores in clinical routine

Abstract: The revised SDAI limits for disease activity and the respective CDAI thresholds proved to be in congruence with the DAS28 disease activity categories in daily clinical routine. The SDAI and the CDAI were found to be more stringent in defining remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 24 publications
3
26
0
8
Order By: Relevance
“…On a practical note, the implementation of tight control into routine care will require quick and simple validated tools for defining treatment targets and monitoring disease activity. Tools such as the CDAI and RAPID-3 appear to meet these requirements; in addition, the CDAI appears not only to provide simplicity but also, as recent studies suggest 38,39 , to be a more stringent tool for assessing remission. However, further studies are still needed to define the most appropriate assessment tools for assessing remission in routine clinical practice, as well as appropriate and achievable clinical targets reflecting tight disease control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On a practical note, the implementation of tight control into routine care will require quick and simple validated tools for defining treatment targets and monitoring disease activity. Tools such as the CDAI and RAPID-3 appear to meet these requirements; in addition, the CDAI appears not only to provide simplicity but also, as recent studies suggest 38,39 , to be a more stringent tool for assessing remission. However, further studies are still needed to define the most appropriate assessment tools for assessing remission in routine clinical practice, as well as appropriate and achievable clinical targets reflecting tight disease control.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between the CDAI and SDAI was found to be almost complete, and the CDAI appeared to correlate strongly with the DAS28 24 . However, results of 2 recent studies suggest that the classification of a patient as being in remission or not depends on the instrument used to define remission 38,39 . The studies assessed and categorized patients according to various disease activity indices, and demonstrated that a greater proportion of patients were assessed to be in remission using DAS28 disease activity criteria compared with using the CDAI and SDAI.…”
Section: Rheumatologymentioning
confidence: 99%
“…Therefore, moderate disease activity (CDAI≤22), low disease activity (CDAI≤10) or remission (CDAI≤2.8) can be calculated upon any combination of the four variables, independent of any other confounding factors. Indeed, Some groups have also suggested that composite indices, such as DAS28 or SDAI may exert problems when used in remission or in LDA states (12)(13)(14)(15). It is imperative to use proper tools to assess remission and LDA, as nowadays, according to the recent EULAR and treat-to-target recommendations, standard care, as well as clinical trials should target these disease states (13,(16)(17)(18)(19).…”
Section: The Cdai Carpetsmentioning
confidence: 99%
“…В последние годы при оценке активности РА и эф-фективности проводимого лечения наряду с DAS 28 [45,46] применяют упрощеннный (SDAI -Simplified Disease Activity Index) и клинический (CDAI -Clinical Disease Activity Index) индексы активности заболевания [47][48][49][50]. В связи с тем что ТЦЗ обладает способностью индуциро-вать выраженное снижение уровня лабораторных марке-ров острой фазы воспаления и в меньшей степени влияет на клинические проявления синовита, CDAI представля-ется более точным методом оценки ответа на терапию ТЦЗ (в частности, достижения ремиссии), чем DAS 28-СОЭ, который может преувеличивать эффективность ТЦЗ из-за существенного вклада значения СОЭ в подсчет дан-ного индекса активности РА [49][50][51].…”
unclassified
“…В связи с тем что ТЦЗ обладает способностью индуциро-вать выраженное снижение уровня лабораторных марке-ров острой фазы воспаления и в меньшей степени влияет на клинические проявления синовита, CDAI представля-ется более точным методом оценки ответа на терапию ТЦЗ (в частности, достижения ремиссии), чем DAS 28-СОЭ, который может преувеличивать эффективность ТЦЗ из-за существенного вклада значения СОЭ в подсчет дан-ного индекса активности РА [49][50][51]. Однако роль остро-фазовых показателей в оценке эффективности ТЦЗ у больных РА по индексам DAS 28 и CDAI недостаточно изучена [51][52][53][54][55][56].…”
unclassified